Impact of pmrA on Cronobacter sakazakii planktonic and biofilm cells: A comprehensive transcriptomic study. (September 2021) - Xu, Zhenbo; Liu, Ziqi; Soteyome, Thanapop; Hua, Jingjing; Zhang, Liang; Yuan, Lei; Ye, Yanrui; Cai, Zhao; Yang, Liang; Chen, Ling; Harro, Janette M.; Kjellerup, Birthe Veno; et al.
Abstract: Cronobacter sakazakii is an emerging opportunistic foodborne pathogen causing rare but severe infections in neonates. Furthermore, the formation of biofilm allows C. sakazakii to persist in different environments. We have demonstrated that the mutator phenotype ascribed to deficiency of the pmrA gene results in more biomass in the first 24 h but less during the post maturation stage (7–14 d) compared with BAA 894. The present study aimed to investigate the regulatory mechanism modulating biofilm formation due to pmrA mutation. The transcriptomic analyses of BAA 894 and s-3 were performed by RNA-sequencing on planktonic and biofilm cells collected at different time points. According to the results, when comparing biofilm to planktonic cells, expression of genes encoding outer membrane proteins, lysozyme, etc. were up-regulated, with LysR family transcriptional regulators, periplasmic proteins, etc. down-regulated. During biofilm formation, cellulose synthase operon genes, flagella-related genes, etc. played essential roles in different stages. Remarkably, pmrA varies the expression of a number of genes related to motility, biofilm formation, and antimicrobial resistance, including srfB, virK, mviM encoding virulence factor, flgF, fliN, etc. encoding flagellar assembly, and marA, ramA, etc. encoding AraC family transcriptional regulators in C. sakazakii . This study provides valuable insights into transcriptional regulation of C. sakazakii pmrA mutant during biofilm formation. Highlights: l A thorough and comprehensive transcriptome analyses of C. sakazakii were conducted.. Transcriptomes of planktonic and biofilm cells during biofilm formation were analyzed. The role of pmrA in biofilm associated cells was revealed . Virulent factors related to motility and antimicrobial resistance were discovered . l This study further aid in insightful elucidation of biofilm formation in C. sakazakii.